Natural fashion tribal decoration from Africa - Silvester, Hans 1938-; Wilson, David H. (New York, N.Y. Thames & Hudson, 2009)
Over the course of numerous voyages to Africa's Omo Valley, Hans Silvester became fascinated by the beauty of the Surma, Mursi, Hamer and Kurma tribes, who share a taste for body painting and extravagant decorations borrowed from nature. This collection of photographs captures these accoutrements.
Originally published in French: Paris : aEditions de la Martiniaere, 2007.
"First published in 2008 in hardcover ... Reprinted in 2009; first published in paperback in 2009"--P. [168].
Keywords: Ethnology -- Omo River Valley (Ethiopia and Kenya) -- Pictorial works; Body painting -- Omo River Valley (Ethiopia and Kenya) -- Pictorial works; Body marking -- Omo River Valley (Ethiopia and Kenya) -- Pictorial works; Body art -- Omo River Valley (Ethiopia and Kenya) -- Pictorial works; Tribal tattoos -- Omo River Valley (Ethiopia and Kenya) -- Pictorial works; Suri (African people) -- Pictorial works; Murzu (African people) -- Pictorial works; Omo River Valley (Ethiopia and Kenya) -- Social life and customs -- Pictorial works